2006
DOI: 10.1001/.405
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia in Human Immunodeficiency Virus Infection: Data From the Women's Interagency HIV Study

Abstract: Background: Neutropenia is well described in individuals infected with human immunodeficiency virus (HIV) and occurs in approximately 10% to 50% of cases. Neither the effect of highly active antiretroviral therapy (HAART) on neutrophil counts nor the significance of neutropenia in terms of survival has previously been evaluated.Methods: The prevalence of neutropenia among 1729 HIV-infected women, followed up as part of the Women's Interagency HIV Study, was evaluated. The CD4 lymphocyte counts, HIV-1 RNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
56
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 21 publications
11
56
1
1
Order By: Relevance
“…10 We now show that this association is evident mainly in those AAs who maintained a low WBC count during disease, suggesting that the genotype-phenotype relationships for the DARC-null state are highly dependent on the cellular milieu. These findings may also help explain the observation that neutropenia, which is found commonly in HIV-infected patients, 2,3 was not associated with decreased survival in a large study of HIV-infected African American women. 2 The basis for the association between DARC Ϫ46C/C and survival advantage during HIV disease remains unknown, but we offer the following possible explanations.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…10 We now show that this association is evident mainly in those AAs who maintained a low WBC count during disease, suggesting that the genotype-phenotype relationships for the DARC-null state are highly dependent on the cellular milieu. These findings may also help explain the observation that neutropenia, which is found commonly in HIV-infected patients, 2,3 was not associated with decreased survival in a large study of HIV-infected African American women. 2 The basis for the association between DARC Ϫ46C/C and survival advantage during HIV disease remains unknown, but we offer the following possible explanations.…”
Section: Discussionmentioning
confidence: 71%
“…These findings may also help explain the observation that neutropenia, which is found commonly in HIV-infected patients, 2,3 was not associated with decreased survival in a large study of HIV-infected African American women. 2 The basis for the association between DARC Ϫ46C/C and survival advantage during HIV disease remains unknown, but we offer the following possible explanations. First, it can be argued that the association of DARC Ϫ46C/C with survival advantage in leukopenic HIV ϩ AAs represents a tautology.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…2 However, studies have shown a direct relationship between severe HIV infection and neutropenia. 1,5 Other possible explanations for infection in patients with HIV disease include the increasing use of corticosteroid treatment, as is used in the treatment of Pneumocystis carinii pneumonia 1,6,7 ; neutropenia-inducing antiretroviral drugs such as zidovudine 1,6 ; and a prolonged life of patients with late-stage HIV disease. 1,6,7 We find 3 interesting features of this case.…”
Section: Discussionmentioning
confidence: 99%